Photonic Technologies for Liquid Biopsies: Recent Advances and Open Research Challenges. Issue 1 (2nd December 2020) - Dell'Olio, Francesco; Su, Judith; Huser, Thomas; Sottile, Virginie; Cortés‐Hernández, Luis Enrique; Alix‐Panabières, Catherine
Abstract: The recent development of sophisticated techniques capable of detecting extremely low concentrations of circulating tumor biomarkers in accessible body fluids, such as blood or urine, could contribute to a paradigm shift in cancer diagnosis and treatment. By applying such techniques, clinicians can carry out liquid biopsies, providing information on tumor presence, evolution, and response to therapy. The implementation of biosensing platforms for liquid biopsies is particularly complex because this application domain demands high selectivity/specificity and challenging limit‐of‐detection (LoD) values. The interest in photonics as an enabling technology for liquid biopsies is growing owing to the well‐known advantages of photonic biosensors over competing technologies in terms of compactness, immunity to external disturbance, and ultrahigh spatial resolution. Some encouraging experimental results in the field of photonic devices and systems for liquid biopsy have already been achieved by using fluorescent labels and label‐free techniques and by exploiting super‐resolution microscopy, surface plasmon resonance, surface‐enhanced Raman scattering, and whispering gallery mode resonators. The current state‐of‐the‐art is critically reviewed here, starting from the requirements imposed by the detection of the most common circulating biomarkers. Open research challenges are considered together with competing technologies, and the most promising paths of improvement are discussed for future applications. Abstract : The emerging field of liquid biopsies could contribute to a paradigm shift in cancer diagnosis/treatment and the recent advances in photonics are supporting and enabling this process. Here the recent advances and open research challenges in the field of photonic technologies for liquid biopsies are critically reviewed, discussing the most promising paths of improvement and the competing technologies .